Hypoxia-ischemia altered expression of glutamate transporter EAAT1 in neonatal rat brain - Tao Feng; Zhang Ling-mei; Sun Feng-yan (Acta Pharmacologica Sinica, 2016)
AIM: To observe altered expression of glutamate transporter EAAT1 after hypoxia-ischemia (H-I) in newborn rat brain. METHODS: Expression levels of EAAT1 were detected with immunohistochemistry method. RESULTS: EAAT1 was a little expressed in cerebral cortex at sham-operated group [(36 +/- 10) cells/slice]. Its expression in cerebral cortex increased at 24 h and 48 h following H-I [(314 +/- 162) cells/slice and (431 +/- 149) cells/slice, respectively], and recovered to control level at 72 h following H-I [(52 +/- 8) cells/slice]. The expression of EAAT1 in the ipsilateral cortex to common carotid artery (CCA) ligation was higher than that in the contralateral cortex. CONCLUSION: After H-I, the expression of EAAT1 had a temporal change in cerebral cortex of newborn rat, and was mainly located in the ipsilateral cortex to CCA ligation.